A Most Improbable Story The Evolution of the Universe, Life, and Humankind (Taylor & Francis, 2023)
This book is a "big history" of the evidence regarding how we came to be. It briefly explores philosophical thought and how our past might affect our future. The text summarizes different perspectives, including the strengths and weaknesses of each. The genesis of our planet is explored, especially the circumstances that must exist for complex life to arise. This brief journey highlights the history of life, the emergence of simple lifeforms, and the evolution of complex creatures, including humans. The book concludes with a discussion of why other humanoids went extinct while our species achieved dominance. The author speculates on potentialities awaiting humankind and our planet.
English
Keywords: Applied ecology; Astronomy, space & time; Biology, life sciences; Earth sciences; Evolution; Geology & the lithosphere; Geophysics; History of science; Humanities; Natural history; Science: general issues; Big History, Emergent Conditions, Evolution of Complexity, Origin of Life